Complex analysis : a functional analytic approach - Haslinger, Friedrich (De Gruyter Textbook, 2018)
In this textbook, a concise approach to complex analysis of one and several variables is presented.After an introduction of Cauchy's integral theorem general versions of Runge's approximation theorem and Mittag-Leffler's theorem are discussed.The fi rst part ends with an analytic characterization of simply connected domains.